2020
DOI: 10.1039/c9lc00761j
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput single-cell cultivation reveals the underexplored rare biosphere in deep-sea sediments along the Southwest Indian Ridge

Abstract: An improved microfluidic streak plate technique relying on droplet microfluidics can advance the exploration of deep-sea rare microbes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…3e). Later, Zhou et al (2018) used the MSP platform under anaerobic conditions to separate several potentially new species and genera from the gut of Reticulitermes chinensis The MSP platform was further improved for long-term cultivation to tackle the problem of rare marine microbe isolation (Hu et al 2020). The improved MSP platform increased the recovery of slow-growing microbes and enabled longterm cultivation of up to five months.…”
Section: High-throughput Single-cell Cultivation For Uncultured Microbesmentioning
confidence: 99%
See 1 more Smart Citation
“…3e). Later, Zhou et al (2018) used the MSP platform under anaerobic conditions to separate several potentially new species and genera from the gut of Reticulitermes chinensis The MSP platform was further improved for long-term cultivation to tackle the problem of rare marine microbe isolation (Hu et al 2020). The improved MSP platform increased the recovery of slow-growing microbes and enabled longterm cultivation of up to five months.…”
Section: High-throughput Single-cell Cultivation For Uncultured Microbesmentioning
confidence: 99%
“…Copyright (2019) Elsevier). d Schematic of semi-automated droplet picker (Fig.3D, and 3F reprinted with permission fromHu et al 2020. Lab Chip 20: 363-372.…”
mentioning
confidence: 99%
“…An improved high-throughput microfluidic streak plate (MSP) platform could be used to accelerate the isolation of micro-organisms from deep-sea environments. Based on the characteristics of slow growth of deep-sea species, a semi-automatic droplet picker was used to improve the isolation efficiency of MSP, whereas improved humidity control enabled long-term cultivation in low-nutrient medium (Hu et al 2020). The results showed that > 90% of the OTUs detected in the MSP pool belonged to the rare biosphere, including 15 potential new species (Hu et al 2020).…”
Section: Perspective Cultivation Strategiesmentioning
confidence: 99%
“…Based on the characteristics of slow growth of deep-sea species, a semi-automatic droplet picker was used to improve the isolation efficiency of MSP, whereas improved humidity control enabled long-term cultivation in low-nutrient medium (Hu et al 2020). The results showed that > 90% of the OTUs detected in the MSP pool belonged to the rare biosphere, including 15 potential new species (Hu et al 2020). Furthermore, I-tip and encapsulation technology based in situ and electrical retrieval approaches of micro-organisms from marine animals are valuable technologies for thraustochytrid isolation (Ben-Dov et al 2009;Jung et al 2014;Koyama et al 2015).…”
Section: Perspective Cultivation Strategiesmentioning
confidence: 99%
“…Various culture-based and culture-independent approaches have attempted to describe both the microbial diversity and the array of metabolic capabilities present in these singular ecosystems, but with more effort devoted to omics-based studies in recent years at the expense of time-consuming culture-based approaches ( Connon and Giovannoni, 2002 ; DeSantis et al, 2007 ; Rinke et al, 2013 ; Chen et al, 2021 ). The cutting-edge approaches for isolation and cultivation of prokaryotes such as microencapsulation, single-cell and droplet-based cultivation, and cell sorting based cultivation (e.g., reverse genomics; Zengler et al, 2005 ; Nichols et al, 2010 ; Boitard et al, 2015 ; Jiang et al, 2016 ; Berdy et al, 2017 ; Terekhov et al, 2018 ; Hu et al, 2020 ; Lewis et al, 2021 ) are very promising but cannot be applied to all microbial taxa as they do not mimic all environmental conditions, and in particular high temperature and pressure. Despite these significant achievements, the vast majority of the genera and phyla of bacteria and archaea on Earth, including those from the deep biosphere, do not have cultured representatives ( Whitman et al, 1998 ; Lloyd et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%